The peculiar behavior of Picha in the formation of metallacrown complexes with Cu(ii), Ni(ii) and Zn(ii) in aqueous solution1. Issue 7 (21st February 2015) - Marchiò, Luciano; Marchetti, Nicola; Atzeri, Corrado; Borghesani, Valentina; Remelli, Maurizio; Tegoni, Matteo
<x xml:space="preserve">Abstract</x> The thermodynamic stability of copper, nickel and zinc metallacrown complexes with picolinehydroxamic acid in aqueous solution has been rationalized.